Safety and Efficacy of Using Staplers and Vessel Sealing Devices for Laparoscopic Splenectomy: A Randomized Controlled Trial. (June 2021) - Fathi, Adel; Elmoatasembellah, Mansour; Senbel, Ahmed; Shahatto, Fayez; Eldamshety, Osama; Shetiwy, Mosab; Abdel Wahab, Khaled; Abouzid, Amr; Setit, Ahmed
Background. Laparoscopic splenectomy (LS) is considered the operation of choice on elective basis for managing patients with certain hematological disorders. Hemostatic control of the splenic pedicle is one of the crucial steps in LS. This study compares the safety and efficacy of using endoscopic staplers and vessel sealing devices to control the splenic pedicle in patients with nonsevere splenomegaly. Methods. Fifty-one consecutive patients with different blood disorders including idiopathic thrombocytopenic purpura (ITP), hypersplenism, and lymphoma were randomized for elective LS. Traditional steps of LS, via lateral approach, were followed, and pedicle control was done with either endovascular gastrointestinal anastomosis stapler (n = 26) or vessel sealing device (Ligasure) (n = 25). Results. No difference was noted with different splenic spans when using either methods of pedicle control ( P = .145). The volume of blood loss was higher in the Ligasure group compared to the staplers group (182 mL vs 131 mL, respectively), but was not statistically significant ( P = .249). Conversion to open was notably higher in the Ligasure group ( P = .034), but the intraoperative complications were comparable in both groups ( P = .357). Conclusion. The use of vessel sealing devices for splenic pedicle control has comparable surgical outcomes compared with the use of endoscopic staplers for LS, but with higher rate of conversion to open surgery.